(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2011)
Infection and antibacterial resistance are important issue in severe burn. This prospective study was carried out in 112 patients who were enrolled from July 2007 to June 2008 in DMCH burn unit (only dedicated burn facility in Bangladesh with a mean annual admission of 869). The aim of this study were to investigate the profile of microorganism and resistance to antimicrobial agents; individuals who were admitted more than 5 days, with partial or full thickness burn developed clinical signs and symptoms of wound infection or pneumonia or septicaemia were included in this study. Nearly 50% of participants were aged 11-30 yrs, the most common type of burn was flame burn and females were the common victims. Bacterial isolates were found in 104 (92.85%) samples and eight (08) swabs were sterile (7.14%). Pseudomonas species was the commonest pathogens (46.42%) followed by Proteus species (21.41%) and Klebsiella species (19.6%). Multiple organisms were found in 38 samples(33.92%). Antibiogram results obtained from ten antimicrobial agents demonstrated that Imipenem was the most efective agent, followed by amikacin and ceftazidime (92.3%, 52.8% and 38.46% sensitive respectively). Hundred percent (100%) of Proteus species were sensitive to imipenem, then amikacin 58.33%; they were highly resistant to cephalosporins (nearly 100%) and ciprofloxacin (83.33%). The resistance of Pseudomonas aeruginosa to anti-pseudomonas agents were exceptionally high. Newer drugs were found to be effective. DOI: http://dx.doi.org/10.3329/jbcps.v29i2.7949 (J Bangladesh Coll Phys Surg 2011; 29: 62-66)